GJA1-20k and Mitochondrial Dynamics - Shimura, Daisuke; Shaw, Robin M. (Frontiers in Physiology, 2022)
Connexin 43 (Cx43) is the primary gap junction protein of mammalian heart ventricles and is encoded by the gene Gja1 which has a single coding exon and therefore cannot be spliced. We previously identified that Gja1 mRNA undergoes endogenous internal translation initiated at one of several internal AUG (M) start codons, generating N-terminal truncated protein isoforms that retain the C-terminus distal to the start site. GJA1-20k, whose translation initiates at mRNA M213, is usually the most abundant isoform in cells and greatly increases after ischemic and metabolic stress. GJA1-20k consists of a small segment of the last transmembrane domain and the complete C-terminus tail of Cx43, with a total size of about 20 kDa. The original role identified for GJA1-20k is as an essential subunit that facilitates the trafficking of full-length Cx43 hexameric hemichannels to cell-cell contacts, generating traditional gap junctions between adjacent cells facilitating, in cardiac muscle, efficient spread of electrical excitation. GJA1-20k deficient mice (generated by a M213L substitution in Gja1) suffer poor electrical coupling between cardiomycytes and arrhythmogenic sudden death two to four weeks after their birth. We recently identified that exogenous GJA1-20k expression also mimics the effect of ischemic preconditioning in mouse heart. Furthermore, GJA1-20k localizes to the mitochondrial outer membrane and induces a protective and DRP1 independent form of mitochondrial fission, preserving ATP production and generating less reactive oxygen species (ROS) under metabolic stress, providing powerful protection of myocardium to ischemic insult. In this manuscript, we focus on the detailed roles of GJA1-20k in mitochondria, its interaction with the actin cytoskeleton, and potential clinical uses of exogenous application of this novel therapeutic peptide.